(untitled) (Bioagro, 2023)
It was studied the pathogenicity of Macrophomina pseudophaseolina isolates in melon seedlings and their influence on protein expression of the crop. For this purpose, two isolates of the fungus were inoculated in Golden and Cantaloupe melon seedlings using the toothpick method. Thirty days after inoculation, disease incidence and severity were assessed using pre-established scales; additionally, stem and root length and fresh weight was evaluated. Protein extraction from plant tissues was performed using the phenol/SDS precipitation method and quantification by the Bradford method. The protein samples were subjected to denaturing polyacrylamide gel electrophoresis (SDS-PAGE). Then, the existence of polymorphism and molecular weight of bands detected in the samples were evaluated. M. pseudophaseolina isolates caused root rot in all inoculated melon seedlings. However, the two isolates exhibited different degrees of aggressiveness to the seedlings. The isolates CMM-4801 and CMM-4771 caused an average symptom severity of 3.40 and 2.60, respectively, in both cultivars. The disease negatively affected seedling development by reducing root length, and stem and root fresh weight. Different polypeptide band patterns were verified between inoculated and control seedlings, indicating different protein expression due to biotic stress caused by the fungus. Moreover, different protein expression patterns were found between the inoculated seedlings, indicating a correlation between pathogen aggressiveness and host response.